An existence result for a semipositone problem with a sign changing weight - Jaffar Ali; R. Shivaji (Abstract and Applied Analysis)
We establish an existence result on positive solution for a class of reaction-diffusion equation with semipositone structure. In particular, our results apply to the diffusive logistic equation with a class of sign changing weight and constant yield harvesting. We establish the result via the method of subsuper solutions.